Click‐Derived Uracil‐Appended Organosilatranyl Scaffolds: Synthesis, Antibacterial Characteristics, Pb2+ Binding and Fabrication of Hybrid Silica Nanoparticles. Issue 1 (2nd January 2020) - Singh, Gurjaspreet; Sharma, Geetika; Sanchita,; Kalra, Pooja; Satija, Pinky; Pawan,; Singh, Baljinder; Aulakh, Darpandeep; Wreidt, Mario
Abstract: Using a simple biocompatible click route Uracil Allied Organosilatranyl frameworks (4 a –4 e ) have been obtained. These uracil tethered silatranes have shown judicious fluorescence as compared to the parent nitrogen heterocycle uracil. Through absorption and fluorescence spectral measurements, it was established that the designed analogues were selective towards Pb 2+ recognition. Furthermore, for the first time hybrid silica nanoparticles (U‐SiNPs) containing a uracil bis‐triazole linkage in the silica framework is reported. The fabricated organosilatrane (4 d ) was subjected to sol‐gel condensation with silica nanospheres for covalent grafting of the organic functionality on to silica. It was of interest that the uracil immobilized nanoparticles presented a high sensing efficacy towards Pb 2+ as compared to the bulk material. Also, to investigate their biological potential, organosilatranes were evaluated against different bacterial strains. Abstract : The current study involves synthesis of Uracil Allied Organosilatranyl frameworks using a simple biocompatible click route. The absorption and fluorescence spectral measurements of the synthesized uracil tethered Silatranes shows their utility for the selective recognition of lead ions. Further, one of the organosilicon derivatives was transmitted over silica to yield organic–inorganic hybrid materials which was highly significant in the field of metal ion detection.